2019
DOI: 10.1186/s12958-019-0480-0
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte alterations in endometriosis: reduced numbers of stem cells and microRNA induced alterations in adipocyte metabolic gene expression

Abstract: Background Endometriosis is an estrogen dependent, inflammatory disorder occurring in 5–10% of reproductive-aged women. Women with endometriosis have a lower body mass index (BMI) and decreased body fat compared to those without the disease, yet few studies have focused on the metabolic abnormalities in adipose tissue in women with endometriosis. Previously, we identified microRNAs that are differentially expressed in endometriosis and altered in the serum of women with the disease. Here we explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…In addition, some studies show that EMS is related to abnormal lipid metabolism, which is manifested by the low body mass index, decreased body fat in human, 33 decreased number of adipocyte stem cells, and disorder of lipid metabolism in the animal model. 34 CDCA and UDCA can improve lipid metabolism and reduce cholesterol saturation in bile, total cholesterol, and low-density cholesterol. [35][36][37] We have speculated that the change in the species abundance and increased CDCA and UDCA levels may be a self-regulation mode of gut microbiota in EMS mice, which can provide the necessary energy to adapt to the inflammatory response by mobilizing lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some studies show that EMS is related to abnormal lipid metabolism, which is manifested by the low body mass index, decreased body fat in human, 33 decreased number of adipocyte stem cells, and disorder of lipid metabolism in the animal model. 34 CDCA and UDCA can improve lipid metabolism and reduce cholesterol saturation in bile, total cholesterol, and low-density cholesterol. [35][36][37] We have speculated that the change in the species abundance and increased CDCA and UDCA levels may be a self-regulation mode of gut microbiota in EMS mice, which can provide the necessary energy to adapt to the inflammatory response by mobilizing lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies show that EMS is related to abnormal lipid metabolism, which is manifested by the low body mass index, decreased body fat in human, 33 decreased number of adipocyte stem cells, and disorder of lipid metabolism in the animal model 34 . CDCA and UDCA can improve lipid metabolism and reduce cholesterol saturation in bile, total cholesterol, and low‐density cholesterol 35‐37 .…”
Section: Discussionmentioning
confidence: 99%
“…The biological function of microRNAs is a promising contemporary concept in the pathophysiology of endometriosis [ 32 ]. Zolbin et al demonstrated that the upregulation (miR-342-3p) or inhibition (Let-7b) of microRNAs seen in endometriosis significantly alters the expression of adipocyte genes related to brown adipocyte differentiation ( Cebpa/b and Ppar-γ ), fat metabolism ( IL- 6, HSL ), and glucose metabolism ( leptin and adipoq ) [ 33 ]. However, this relationship does not seem to be reciprocal: Holdsworth-Carlson found no significant impact of obesity on endometrial gene expression, even after stratification for BMI or severity of endometriosis [ 34 ].…”
Section: Searching In the Genes How Obesity And Endometriosis Interact At A Genetic Levelmentioning
confidence: 99%
“…All 14 patients in this study had PEM secondary to a lateral episiotomy or laceration and the incubation period ranged from 2 mo to 69 mo after surgery. Current studies indicate that the occurrence and severity of pelvic EM are negatively correlated with BMI and pelvic EM[ 9 , 10 ]. However, due to the lag in diagnosis of pelvic EM, there are no reports on the incubation period of pelvic EM and BMI.…”
Section: Discussionmentioning
confidence: 99%